Peran Guru dalam Pengajaran Pendidikan Multikultural: Inisiasi dan Praktek - Munaya Ulil Ilmi; Indah Mayangsari; Fisca Artita Dewi (Kayon Media, 2021)
Indonesia is a multicultural nation that has very high diversity. This diversity can be a potential for the nation's progress as well as its decline, depending on the quality of the management of this heterogeneity. It is undeniable that conflicts with the background of ethnicity, religion and race between groups (SARA) still often occur in Indonesia. This shows the importance of strengthening multicultural education in Indonesia. This study aims to review the urgency of multicultural teaching in schools. The research method used is literature study, explaining the phenomena that occur based on scientific studies that have been done before. Based on the discussion, it can be concluded that multicultural education in schools is very important to do so that students are able to accept all differences from an early age. In this process, the teacher has a very big role. Teachers must be able to master the teaching methods and concepts of multicultural learning itself. The teaching of multicultural education is so that students are able to be active and critical in facing all differences ranging from religion, language, ethnicity, gender, and social status in society.